Análise da geração de resíduos da construção civil da cidade de João Pessoa-PB. - Pimentel, Ubiratan Henrique Oliveira (2013)
The waste from the construction industry have grown noticeably, throughout the world, not being different in Joao Pessoa. This fact is a serious issue to the civil construction industry, regulatory agencies, the population and the environment. It turns out that the waste could be reused or recycled in the construction sites of the buildings where they are generated, and your correct management minimize your output, contributing for the reduction of degradation of the environment and, consequently, reducing the consumption of natural raw materials, many of which are irreplaceable. In this paper, we present the results of an investigation into the generation of construction Waste (RCC) of class A in João Pessoa, analyzing the construction areas performed between the years 2000 to 2010, identifying neighborhoods that have grown in population and housing aspects, as well as the mass of the RCC for they generated in the municipality. The goal is to estimate the amount of RCC in João Pessoa, analyzing the volume generated, your destination since its source of generation to USIBEN (processing plant construction and demolition waste) and, yet, the difference between the amount generated and that reaches the USIBEN estimated the fraction of irregular deposits. The study found a generation of 0.06 m3/m2 and 60.4 kg/m2. Found volume of RCC only 57.8% is being directed to USIBEN. Various points were of irregular deposition of RCC in João Pessoa, being the five largest analyzed regarding the distance from the neighborhoods of greatest generation compared to distance to USIBEN.